AUTHORITY, DISCRETION, AND INCLUSION: A SOCIO-LEGAL ANALYSIS OF MARRIAGE REGISTRARS AND SENSORY DISABILITIES IN INDONESIA - Ni'ami, Mohammad Fauzan; Saifullah, Saifullah; Fakhruddin, Fakhruddin (Masalah-Masalah Hukum, 2025)
This study explores the role of marriage registrars in Indonesia when officiating marriages involving individuals with sensory disabilities. Focusing on Jombang Regency, East Java, the research investigates the legal actions and motivations of registrars in ensuring the compliance of marriage procedures for sensory-disabled couples. Using a socio-legal approach and Max Weber’s theory of action, the study identifies two models of action: legal authoritative actions and legal discretionary actions. Registrars, as legal authorities, enforce marriage registration regulations, ensuring that prospective brides and grooms with sensory disabilities meet the required criteria. However, due to the absence of specific regulations regarding marriage registration for sensory-disabled individuals, registrars exercise discretion, modifying procedures to accommodate communication limitations. The study finds that registrars’ motivations for these actions are guided by legal rationality, ensuring legal certainty in authoritative actions, and legal responsiveness, aiming to uphold the rights of individuals with sensory disabilities. The findings highlight the need for legal reforms in family law to integrate disability rights into marriage registration regulations, as registrars face challenges in officiating marriages for sensory-disabled individuals within the existing legal framework. The research contributes to the understanding of how legal actors, such as marriage registrars, balance legal obligations with the need for flexibility in ensuring inclusive practices for marginalized groups.